ANALISIS FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR MATA PELAJARAN DI SMP NEGERI 03 KEPANJEN - Kardisius Agot; Rusno rusno; Walipah Walipah (Jurnal Riset Pendidikan Ekonomi, 2019)
The purpose of this study is 1. to find out and analyze what factors influence the success of social studies learning achievement in students of SMP Negeri 03 Kepanjen Malang Regency.2. To find out and analyze the dominant factors that influence the learning achievement of social studies subjects in SMP Negeri 03 Kepanjen. The population in this study were students of class VII in SMP Negeri 03 Kepanjen whose IPS scores were less than KKM, totaling 186 students. And the sample is 48 students. The data collection technique used was Questionnaire Data obtained were analyzed by factor analysis techniques. This type of research uses factor analysis using Bartlett's lest of Sphericity. Based on the results of the study showed that there were 15 (fifteen) learning achievement factors formed, these factors were as follows: (1) family environmental factors, 17.21% (2) 7.80% material mastery factors. (3) class atmosphere factors, 6.80%. (4) learning source factors are 5.95%. (5) student activeness factor is 4.68%. (6) learning interest factors are 4.48%. (7) school environment factors, 3.92%. (8) physiological factors of students, 3.68%. (9) learning method factors 3.39%. (10) community environmental factors 3.21%. (11) the teacher discipline factor is 2.99%. (12) the method of teaching methods of teachers is 2.85%. (13) student readiness factor 2.68%. (14) learning facility factors 2.56% (15) curriculum factors 2.35%. The factor which gave the biggest contribution was the family environment factor, which was 17.21%. The smallest contribution is given by the curriculum factor which is 2.35%.